Diminished ovarian reserve and ectopic ovaries in patients with Mayer-Rokitansky-Küster-Hauser syndrome candidates for Uterus Transplantation: our experience - Basilio Pecorino; Giuseppe Scibilia; Placido Borzì; Maria Elena Vento; Pierfrancesco Veroux; Paolo Scollo (IMR Press, 2021)
Background: Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is a congenital disease characterized by variable degrees of utero-vaginal agenesis. A diminished ovarian reserve and ectopic ovaries are common in these patients. The objective of this study is to highlight the issues relating to assisted reproduction in patients with MRKH syndrome who are candidates for Uterus Transplantation and to describe alternative methods to the classic transvaginal oocyte retrieval. Methods: In Italy, the Research Project for Uterus Transplantation from brain-dead donor started on 14/06/2018 (n. 1438/CNT2018). The potential recipients underwent to clinical evaluation, laboratory and instrumental tests to achieve eligibility for transplantation, ovarian stimulation and oocytes retrieval at the Obstetrics and Gynecology Unit of the Cannizzaro Hospital of Catania (Italy). A retrospective analysis of all patients affected by MRKH syndrome who are candidates for uterus transplantation was performed in order to highlight the problems encountered in assisted reproduction due to poor ovarian reserve or extra-pelvic gonads. Results: 15 of 64 patients (23%) were excluded after the first visit due to the poor ovarian reserve and/or ectopic ovaries. A 27-years old patient with MRKH syndrome type 2, with extra-pelvic ovaries and good ovarian reserve underwent ultrasound-guided and laparoscopically assisted transvaginal and transabdominal oocyte pick-up, with total retrieval of 12 oocytes and no short or long-term complications. Conclusion: Laparoscopically assisted oocyte retrieval is a feasible technique that can overcome some limitations for inclusion on waiting list for Uterus Transplantation, such as ectopic ovaries.